Supplementary Table 3 from Metastatic Prostate Cancers with BRCA2 versus ATM Mutations Exhibit Divergent Molecular Features and Clinical Outcomes - Justin Hwang (15925675) (2025)
Comparisons of WTS profiles between ATMm and BRCA2m to the HRP group.